The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1108/k-01-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling critical leadership competences for junior high school principals

Abstract: Purpose Based on generic reviews of research on school leadership, this study aims to conceptualize an emerging leadership competence model for further prioritizing school leadership training needs by decision-making trial and evaluation laboratory (DEMATEL)-based analytic network process (ANP). Targeting at a specific group of junior high school principals in Taiwan, the synthesized prioritization of core competences and competence indicators computed by DEMATEL-based ANP can be used as a blueprint for system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Other study found out that among the hypothesized variables are team orientation, stability. Transactional leadership, decentralization, formalization and top management support have an influence on organizational commitment [7]. According to Hair et al [8] suggested that the independent variables of organizational culture show how integrity and learning from culture which seems to be the opposite of a set of organizational and individual values to balance the cultural paradox and manage culture effectively, an intensive culture of knowledge has a reinforcing effect on the relationship between the knowledge process and employee creativity having a highly influential public service performance variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other study found out that among the hypothesized variables are team orientation, stability. Transactional leadership, decentralization, formalization and top management support have an influence on organizational commitment [7]. According to Hair et al [8] suggested that the independent variables of organizational culture show how integrity and learning from culture which seems to be the opposite of a set of organizational and individual values to balance the cultural paradox and manage culture effectively, an intensive culture of knowledge has a reinforcing effect on the relationship between the knowledge process and employee creativity having a highly influential public service performance variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, DEMATEL assists the composite development group to establish aspects of the project that warrants enhancement. The following steps are taken in the execution of the DEMATEL approach (Tang, 2018;Bhanot et al, 2020):…”
Section: Research Methods 31 Dematelmentioning
confidence: 99%
“…This paper presents a method to estimate the ISRS in ESC through integrating DEMATEL and ANP. DEMATEL is popularly used for capturing the underlined or hidden interrelationships between decision criteria (Trujillo-Gallego and Sarache, 2019;Gupta and Barua, 2018; BIJ 1264 27,3 Tang, 2018;Ranjan et al, 2016). ANP on the other hand was used to access or calculate the priority values (PV ), i.e., to estimate the importance level of various decision criteria or indicators (Raut et al, 2018;Chand et al, 2018;Wudhikarn et al, 2015).…”
Section: Proposed Methodologymentioning
confidence: 99%